Strategies for the Development of Bioprotective Cultures in Food Preservation - Luana Virgínia Souza; Evandro Martins; Isabella Maria Fernandes Botelho Moreira; Antônio Fernandes de Carvalho (International Journal of Microbiology)
Consumers worldwide are increasingly demanding food with fewer ingredients, preferably without chemical additives. The trend called “Clean Label” has stimulated the development and commercialization of new types of bioprotective bacterial cultures. These bacteria are not considered new, and several cultures have been available on the market. Additionally, new bioprotective bacteria are being identified to service the clean label trend, extend the shelf life, and, mainly, improve the food safety of food. In this context, the lactic acid bacteria (LAB) have been extensively prospected as a bioprotective culture, as they have a long history in food production and their antimicrobial activity against spoilage and pathogenic microorganisms is well established. However, to make LAB cultures available in the market is not that easy, the strains should be characterized phenotypically and genotypically, and studies of safety and technological application are necessary to validate their bioprotection performance. Thus, this review presents information on the bioprotection mechanisms developed by LAB in foods and describes the main strategies used to identify and characterize bioprotective LAB with potential application in the food industry.